MULTISENSOR MICROSYSTEM FOR MEASURING THE CONCENTRATION OF GASES CO, H2 , C3 H8 , CO2 - O. G. Reutskaya; I. A. Taratyn; Y. M. Pleskachevsky (Приборы и методы измерений)
Manufacture of module of chemical sensors on a single chip is one of the promising directions in the development of gas sensory. The aim of this work was development of construction of multisensor microsystem enabled to retain the characteristics of a single sensor and its dimensions and, at the same time, to reduce power consumption and cycle time of measuring concentration of gases CO, H2 , C3H8 , CO2 in the environment. Multisensor microsystem consists of four detached sensors placed on a single substrate of nanostructured aluminum oxide. The use of through-holes and the dielectric substrate itself in microsystem topology reduced power consumption of gas microsystems. We have devised a method of measuring sensitivity of foursensor microsystem to the concentration of gases CO, H2 , C3H8 , CO2. A full cycle of measuring gases concentration consisted of the time required for preliminary heating of all sensors of the microsystem (5 s), the heating time of each of the sensors sequentially (5 s) and time required to measure resistance for each sensor (80 s). The measured results show that the reaction time of multisensor microsystem when exposed to gases – H2 at a concentration of 0,001 %, CO2  1 %, СО – 0,02 %, C3H8 – 0,01 % does not exceed 90 s for full measurement cycle. Sensitivity value at power consumption of < 150 mW makes up 48–64 % for H2 , 32– 36 % for CO2 , 20–29 % for СО, 68–78 % for C3H8 . The proposed method to control sensitivity of multisensor microsystem to the concentration of gases CO, H2 , C3H8 , CO2 allows performing measurements within 90 s while the measurement cycle by a single sensor in pulse heating mode is 2 min, in continuous heat mode – 5 min. Maximum power consumption of the microsystem does not exceed 150 mW. Microsystems allow measuring lower concentrations of detected gases.